2014
DOI: 10.1021/om5002809
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches toward Ferrocene–Guanine Conjugates: Synthesis and Electrochemical Behavior

Abstract: Different substituted ferrocene−guanine conjugates were prepared, and their electrochemical behavior was investigated. A new approach for the introduction of ferrocene in guanine's 9-position through a quite effective S N 1-type reaction was disclosed. The electrochemical behavior of the various derivatives can be used as standard for the quantification and analysis of DNA strands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Keeping in mind potential applications of the redox‐active XNA, the ferrocenyl–nucleobase conjugates, and the ferrocenyl nucleosides, the electrochemical behavior of compounds 1 – 5 was investigated by means of cyclic voltammetry (CV). The electrochemical measurements were carried out in an atmosphere of argon using a solution of anhydrous dimethyl sulfoxide (DMSO) that contained weakly coordinating [Bu 4 N][B(C 6 F 5 ) 4 ] (0.1 mol L −1 ) as supporting electrolyte .…”
Section: Resultsmentioning
confidence: 99%
“…Keeping in mind potential applications of the redox‐active XNA, the ferrocenyl–nucleobase conjugates, and the ferrocenyl nucleosides, the electrochemical behavior of compounds 1 – 5 was investigated by means of cyclic voltammetry (CV). The electrochemical measurements were carried out in an atmosphere of argon using a solution of anhydrous dimethyl sulfoxide (DMSO) that contained weakly coordinating [Bu 4 N][B(C 6 F 5 ) 4 ] (0.1 mol L −1 ) as supporting electrolyte .…”
Section: Resultsmentioning
confidence: 99%
“…Ferrocenyl XNA nucleotides have been utilized as building blocks for construction of short redox‐active nucleic acid strands and ferrocenyl guanine conjugates have been used as standards for the quantification and analysis of DNA strands . Furthermore, it has been shown that specifically designed, chelating oligonucleotides can self‐assemble into metal‐mediated nanowire structures .…”
Section: Resultsmentioning
confidence: 99%
“…Decamethylferrocene was used as an internal standard at the end of every measurement. Details have been provided elsewhere . Cyclic voltammetry of Salophen complexes spin‐coated on HOPG was performed in a standard three‐electrode electrochemical cell, in which Ag/AgCl, KCl (3 m ) was the reference electrode, Pt spiral is the counter and HOPG acts as working electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Details have been provided elsewhere. [38] Cyclic voltammetry of Salophen complexes spin-coated on HOPG was performed in as tandard three-electrode electrochemical cell, in which Ag/AgCl, KCl (3 m)w as the reference electrode, Pt spiral is the counter and HOPG acts as working electrode. Measurements were carried out in distilled water with KCl 0.1 m as supporting electrolyte.…”
Section: Experimental Section Electrochemistrymentioning
confidence: 99%